If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -2) = 6(y + -1) + -3y Reorder the terms: 4(-2 + y) = 6(y + -1) + -3y (-2 * 4 + y * 4) = 6(y + -1) + -3y (-8 + 4y) = 6(y + -1) + -3y Reorder the terms: -8 + 4y = 6(-1 + y) + -3y -8 + 4y = (-1 * 6 + y * 6) + -3y -8 + 4y = (-6 + 6y) + -3y Combine like terms: 6y + -3y = 3y -8 + 4y = -6 + 3y Solving -8 + 4y = -6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -8 + 4y + -3y = -6 + 3y + -3y Combine like terms: 4y + -3y = 1y -8 + 1y = -6 + 3y + -3y Combine like terms: 3y + -3y = 0 -8 + 1y = -6 + 0 -8 + 1y = -6 Add '8' to each side of the equation. -8 + 8 + 1y = -6 + 8 Combine like terms: -8 + 8 = 0 0 + 1y = -6 + 8 1y = -6 + 8 Combine like terms: -6 + 8 = 2 1y = 2 Divide each side by '1'. y = 2 Simplifying y = 2
| -1=7+8p | | g(x+2)=x^2-10x-21 | | 4x+8=14+10 | | 8(x-6)=-8(x+6) | | 9+8=-39 | | -6(7)+8y=-24 | | 7x=4(x-9) | | b-8+4b=23 | | 6x-15=-36 | | 3x^2-2x=-4 | | -3(x+4)+7(2x-1)=2 | | -3x+11=-2(3x+2) | | 2(x-5)=3x-10-x | | 0.60x+0.15(100)=0.30(42) | | 10y+2=-12y | | 9c+6-8c=19 | | 6(2x+1)+3x=-24 | | 2(2x+2)+2x=52 | | -8(-x+10)=-4(-3x-7) | | 2-7=-5 | | -5(x-8)-4=36 | | 8y-(6y+3)=9 | | 3(x+2)-2x=4(x+3) | | -11d+17d=-12 | | 8x+8-2x=-22 | | -3.1m-5.3+12.9m=-7.9+9.8m+2.6 | | 8-4=-20 | | (2x-12)=(x-3) | | x+-0.9=3.9 | | 13n+10n=-15 | | 86x+172y=3990 | | (4x-10)/5=(2x-5)/6 |